Fostering Students' Social Tolerance in Sociology Learning in High School Harapan Mandiri - Fritz Hotman Syahmahita Damanik (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to determine the fostering of students' social tolerance in sociology learning at SMA Harapan Mandiri. The method used in this study is qualitative with a descriptive approach, data collected through observation, interviews, and documentation at SMA Harapan Mandiri. Data analysis uses reduction, presentation, and conclusions. The results showed that a holistic approach through an inclusive curriculum, tolerance case studies, guided discussions, use of diverse learning resources, collaborative activities, empathy skills training, tolerant behavior models, and personal guidance significantly contributed to the formation of students' social tolerance attitudes at SMA Harapan Mandiri